Mineral and Vitamin Contents of Monodora myristica (African Nutmeg) Seeds from Nsukka, Enugu State, Nigeria - Nkwocha, C.C.; Okagu, I.U.; Chibuogwu, C.C. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Monodora myristica is a perennial, edible plant, widely used in many parts of the world as a spice for local delicacies and as a part of polyherbal formulations for disease management. To our knowledge, there is paucity of data on the nutritional content of M. myristica seeds from Nsukka, an urban town in Enugu State, Nigeria, with wide availability of the plant. This study was undertaken to determine the mineral and vitamin contents of M. myristica (African nutmeg) seeds from Nsukka, Enugu State, Nigeria. Materials and Methods: Seeds of M. myristica used were deshelled, oven-dried and ground into fine powder. The powdered sample was subjected to mineral analysis using atomic absorption spectrometry and the vitamin content was determined using spectrophotometry. Results: The mineral analyses showed that the seed had the highest calcium content (333.33±1.4 mg/100 g). Other minerals found were magnesium (182.99±0.03 mg/100 g), manganese (10.35±0.13 mg/100 g), sodium (5.47±0.31 mg/100 g), lead (0.00 mg/100 g), nickel (1.43 ±0.25mg/100 g), iron (90.0±0.01 mg/100 g), zinc (3.73±0.2 mg/100 g) and chromium (9.26±0.55 mg/100 g). Vitamin C had the highest vitamin concentration at 9.88±1.72 mg/100 g; the other concentrations were as follows: vitamin B12 (0.17±0.03 mg/100 g), vitamin B3(0.68±0.14 mg/100 g), vitamin B9 (0.22±0.04 mg/100 g), vitamin B6 (0.54±0.07 mg/100 g), vitamin B1 (5.63±0.92 mg/100 g), vitamin B2 (0.82±0.65 mg/100 g), vitamin A (0.92±0.07 mg/100 g) and vitamin E (5.50±1.41 mg/100 g). Conclusion: The results showed that the seed is rich in minerals and vitamins and the levels vary compared to those found in the literature, which could be attributed to the different soil types and the nutritive state of the soil where the plant is cultivated.